2011
DOI: 10.2113/gscpgbull.59.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe Canyon and Belly River coal measures, south central Alberta: Part 2 -- Modeling reservoir properties and producible gas

Abstract: The gas reserves and well spacing units in the Horseshoe Canyon-Belly River Formation coal measures in Alberta are assigned based on gas-in-place determined by canister desorption tests of coal following ERCB (2010) guidelines. However, substantial gas, which is not measured by desorption tests, also occurs in the free state within the coals as well as adsorbed and in the free state within adjacent fine-grained strata (referred to here as shales) interbedded with the coals. A series of laboratory experiments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Numerical simulations from CMG-GEM have previously been used for predicting the producibility of unconventional gas reservoirs (ex. [3]- [8]) including the [10]). (b) Mannville coal distributions in Alberta shown as the grey region and the location of the Corbett fairway is shown as the red rectangle (modified from [11]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations from CMG-GEM have previously been used for predicting the producibility of unconventional gas reservoirs (ex. [3]- [8]) including the [10]). (b) Mannville coal distributions in Alberta shown as the grey region and the location of the Corbett fairway is shown as the red rectangle (modified from [11]).…”
Section: Introductionmentioning
confidence: 99%
“…thickest) coal seam in a wet reservoir. The commingled production of shales when the coal seams are perforated in a vertical well within the dry Horseshoe Canyon and Belly River coal measures was previously investigated using CMG-GEM [10]. Reference [10] found that including gas-bearing shales interbedded between coal seams increased the cumulative gas production by 144% after 50 years and resulted in reconsideration of optimum well spacing units.…”
Section: Introductionmentioning
confidence: 99%
“…Current production is about 800 mmcf/day, almost all of which is from a fairway of wet coals (S w > 0) about 4000 km 2 in central Alberta , referred to as Corbett (Figure 1). In the Corbett area, coal gas is produced from about 200 multilateral horizontal wells, spaced mainly at 3 -4 wells per mile 2 (2.59 km 2 ; Figure 1). The horizontal wells are completed mainly in the thickest seam in the succession and are orientated NW-SE, N-S, and E-W with the [2]); (b) Mannville coal distribution in Alberta shown as the grey region and the location of the Corbett fairway, shown as the red rectangle (modified from [3]); (c) Schematic diagram of a single horizontal well, 1000 -1600 m long, drilled and completed in the main (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the Corbett area, coal gas is produced from about 200 multilateral horizontal wells, spaced mainly at 3 -4 wells per mile 2 (2.59 km 2 ; Figure 1). The horizontal wells are completed mainly in the thickest seam in the succession and are orientated NW-SE, N-S, and E-W with the [2]); (b) Mannville coal distribution in Alberta shown as the grey region and the location of the Corbett fairway, shown as the red rectangle (modified from [3]); (c) Schematic diagram of a single horizontal well, 1000 -1600 m long, drilled and completed in the main (i.e. thickest) coal seam in the sequence (modified from [4]); (d) Cumulative resource by BCF/section for the P10, P50, and P90 gas contents showing the contribution of the main coal seam, all coal seams > 0.15 m, and the shales (variably organic mudstones) for the Mannville coal measures (modified from [5]); (e) Location of horizontal wells (black radiating lines) and vertical wells (black dots) in the Corbett fairway; (f) The variation in production with lateral azimuth for horizontal wells located in the red square of plot (e).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the parameters varies with production, often in Figure 1. (a) Schematic cross-section across the Western Canadian sedimentary basin (modified from [8]). (b) Mannville coal distribution in Alberta shown as the grey region and the location of the Corbett fairway, shown as the red rectangle (modified from [9]).…”
Section: Introductionmentioning
confidence: 99%